2019
DOI: 10.3390/molecules24030484
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Docking Studies and Monoamine Oxidase Inhibition of a Small Library of 1-acetyl- and 1-thiocarbamoyl-3,5-diphenyl-4,5-dihydro-(1H)-pyrazoles

Abstract: New N-acetyl/N-thiocarbamoylpyrazoline derivatives were designed and synthesized in high yields to assess their inhibitory activity and selectivity against human monoamine oxidase A and B. The most important chiral compounds were separated into their single enantiomers and tested. The impact of the substituents at N1, C3 and C5 positions as well the influence of the configuration of the C5 on the biological activity were analyzed. Bulky aromatic groups at C5 were not tolerated. p-Prenyloxyaryl moiety at C3 ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In this work, DCH/CO-RMs presenting different “drug spheres” are reported. Ten compounds were synthesized according to the general procedure reported in Figure 1 and Figure 2 based on procedures published in our previous works [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, DCH/CO-RMs presenting different “drug spheres” are reported. Ten compounds were synthesized according to the general procedure reported in Figure 1 and Figure 2 based on procedures published in our previous works [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pyrazolines are reduced pyrazoles, and several studies have shown these chiral molecules have remarkable MAO inhibitory properties (Figure ). Recently, Ucar et al synthesized some 1‐ N ‐substituted thiocarbamoyl‐3‐phenyl‐5‐thienyl‐2‐pyrazoline derivatives and reported compound 35 selectively inhibited AChE (IC 50 = 0.09 µM) and MAO‐B (IC 50 = 43 µM).…”
Section: Overview Of Dual‐acting Mao and Che Inhibitorsmentioning
confidence: 99%
“…Different pyrazoline derivatives were synthesized and screened for their MAO inhibitory activities. Especially, substitution at 1, 3, and 5 positions of the pyrazoline nucleus displayed a significant activity towards MAO enzyme . There are also many thiazole compounds found to be effective against MAO enzymes in the literature …”
Section: Introductionmentioning
confidence: 99%